Dairy farms at an advanced stage in their agroecological transition show higher environmental and socio-economic performance - Orounladji, Boko Michel; Sib, Ollo; Kouakou, Patrice Koffi; Darmaun, Maryline; Sanogo, Souleymane; Vall, Eric (Frontiers in Sustainable Food Systems, 2025)
In Burkina Faso, the growing demand for milk prompts dairy farmers to pursue solutions that improve their production while maintaining profitability and sustainability. This study aimed to analyse the link between the level of agroecological transition achieved by dairy farms in the Bobo-Dioulasso milkshed area and their multidimensional performance. To address this issue, 204 dairy farms were assessed in the Bobo-Dioulasso milkshed area according to their level of progress in the agroecological (AE) transition, using the Holistic Localised Performance Assessment for Agroecology (HOLPA) tool. A typology of the dairy farms was produced according to their level of progress in the AE transition. Averaged scores for all questions in the HOLPA tool relating to the 13 principles of agroecology were used to rate each farm on a 5-point Likert scale, from 1 (Non-AE) to 5 (Very Strong AE). Performance was then compared according to these score levels. Results indicate that the dairy farms studied are mostly at the beginning (Non-AE: 7%, Weak AE: 54%, Moderate AE: 33%, and Strong AE: 6%) of their AE transition. Our findings suggest that dairy farms which have adopted more advanced AE practices demonstrate improved environmental, social and economic performance compared to conventional or less transitioned farms. The most AE dairy farms stand out on several key performance indicators. In terms of environmental performance, the most AE dairy farms achieve higher scores for crop diversity and natural resource and land management. In terms of social performance, the most AE dairy farmers share more knowledge about agroecology and natural resources, report higher levels of household satisfaction, and perceive trade associations as efficient. In terms of economic performance, the most AE dairy farms enjoy more stable and diversified income streams, which may reflect their greater resilience. With regard to agronomic performance, the most AE dairy farms perform better in terms of organic manure and fodder production. However, heavy reliance on labor and low crop productivity (e.g., for maize, sorghum, millet, rice, and cowpea) have been identified as key challenges to the AE transition and the sustainability of dairy farms. The findings of this study justify the implementation of several policy measures to support farmer training in AE on fodder and organic manure production, and natural resources management, to guaranty a better access to forages seeds and agricultural equipment to manage manure production, to increase the skills of farmers community in collective natural resources management in order to strengthen and accelerate the AE transition and enhance the resilience of the dairy sector in Burkina Faso. This study provides robust evidence to help improve public policy, guide dairy industry strategies, and support the agroecological transition in the Bobo-Dioulasso milkshed area.